Na rota dos badges: recompensas inspiradas em Super Mario no ensino de requisitos e programação - Cruz, Eric Lenin Lucena de Sousa (2025)
Programming is an essential component in computing courses, being present in several disciplines and playing a fundamental role throughout the degree. Likewise, understanding software requirements is crucial, serving as a basis for subsequent disciplines and future professional activities. However, teaching these contents can become challenging and often demotivating for students, harming academic performance and the consolidation of knowledge. Gi ven this scenario, this work presents an experience report on the application of gamification as a pedagogical tool in the subjects of Programming Laboratory and Introduction to Software Processes and Requirements. The methodology consisted of creating a card of themed badges inspired by the universe of the game Super Mario, with achievements associated with the stages of the final pro ject of each discipline. The proposal encouraged active participation, increased student engagement and motivation, resulting in better academic performance and a more positive learning experience.